The impact of three religious groups on the changing roles of Meranao women : a study of Tabligh Jama'ah, Markazosshahab fil-Filibbin and Ahl al-Bayt - Barra, Ni'mah Ummu Hani Didaagun (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This research analyses the impact of three religious groups, Tablīgh Jama'ah, Markazosshabab fil Filibbin and Ahl al-Bayt in the city of Marawi, Lanao del Sur, Philippines, on the changing roles of Meranao women. Of necessity, this research examines the coming of Islamic resurgence in the Philippines and the traditional to contemporary roles played by Meranao women. This study is based upon primary and secondary sources such as books, articles, journals, newspapers, government reports, non-governmental organization's reports, policy statements, and press releases. The researcher also carried out interviews with key figures of the three religious groups and distributed questionnaires to four hundreds and fifty (450) individuals from different walks of life. The findings reveal that the three religious groups impacted Meranao women including the secular-oriented women. The interviews and the responses to the questionnaire items also show the impact of these religious groups in terms of donning hijab and participating in Islamic religious assembly or activities not just at the local but also at the national level. The study emphasises the necessity of cooperation and coordination among the religious groups and Meranao women's organizations in promoting comprehensive and equitable development of all segments of the Islamic Ummah.